Proposed Marketing Strategy to Increase The Number of Students of Study Programs For Yarsi University - Amalia, Rizki; Purwanegara, Mustika Sufiati (The Indonesian Journal of Business Administration, 2013)
Since the establishment of School of Medicine in 1967 YARSI which consists of only one medicine faculty until they changed the status to YARSI University in 1989 until now, with five faculties, many achievements have been reached and can be proud of. Among them are the best private medical college in Jakarta, and even nationally recognized. However, these conditions are not followed outside medicine faculty where less students when compared to medicine faculty. To find the root problems that facing by YARSI university and its solutions, a preliminary step is collecting data on both primary and secondary data. Secondary data used to analyze the macro environment, the porter's five force analysis, competitors analysis, segmenting, targeting and positioning, and marketing mix. Primary data used to consumer analysis with distributing questionnaire to and YARSI University student. The result analysis are YARSI university does not have a strong marketing strategies and less optimal promotions so that could cause low awareness. Therefore, the proposed marketing strategy in accordance with current conditions as well as marketing communications strategy to increase the number of students who enroll in all YARSI university courses. Keywords: higher education, YARSI, marketing strategy